Between desire and passion Teresa de Cartagena - Kim, Yonsoo (Leiden Brill, 2012)
Teresa de Cartagena's distinctive writing locates her place in a line of European women intellectuals, presenting an indispensible dialogue among her peers of the early modern age. Tracing her predecessors' achievements, we can appreciate the multifaceted characteristics of Teresa's writings.
Introduction: mapping Teresa de Cartagena amongst European women writers -- Writing to survive and heal: Teresa de Cartagena's life and works -- Writing with traditional discourses -- Writing to alleviate and understand: first part of Arboleda de los enfermos (Grove of the inf.irm) -- Writing to instruct and illuminate: second part of Arboleda de los enfermos (Grove of the inf.irm) -- Writing to give voice: defense of women -- Writing with irony: defense of woman's voice and discourse in Admiracion operum Dey (Wonder at the works of God).
CSSP-7997 donated by Brill Publishers through SPi Global Foundation, Inc.
Keywords: Teresa -- de Cartagena -- active 15th century -- Criticism and interpretation; Women -- Spain -- History -- Middle Ages, 500-1500.; Suffering in literature; Sadness in literature